PROJECT BASED ONLINE MEETING APPLICATION FOR SOFTWARE DEVELOPMENT COMPANY - Yohanes Ekodono; Anjik Sukmaaji; Teguh Sutanto (Jurnal Sistem Informasi Universitas Dinamika, 2014)
Development methodology in software development companies becomes the most important component to drive and standardize the development process. Several methodologies used for developing software project, like project based development, required periodic meetings besides the developing and production times. These meetings were supposed to be held frequently in purpose to determine which steps should be taken or even possible to be done, reporting, problem solving, and proposing features. Yet, those meeting’s aims have not been facilitated by existing discussion medias. Most existing discussion medias were not built for this methodology. So that, this condition makes this development methodology users, find their difficulties to either holding discussions or even collaborate.The purpose of doing this research is a respond to those difficulties, by creating a real time meeting media that can facilitates project based development method. The application uses the scrum development as the meeting pattern, because scrum itself is a project based development methodology. Moderation stuffs have been added to support the meeting process. This meeting media can be able to held daily meetings and collaboration based on each project. The collaboration consists of features proposing, voting, chatting, and file and code sharing. While the daily meeting consists of problem solving, reporting, and other collaboration features as mentioned above. This media also can save activities history for each meeting, listed and sorted by each development step, that can be used for completion tracking of a project. Therefore, with this media, project based development methodology meetings can be facilitated.